[PP.06.08] PREVALENCE AND CLINICAL OUTCOMES OF WHITE COAT AND MASKED HYPERTENSION COMPARED TO NORMOTENSION AND SUSTAINED HYPERTENSION. (September 2017) - Tocci, G.; Simonelli, F.; Attalla, N.; D'Agostino, M.; Presta, V.; Figliuzzi, I.; Gallo, G.; Costanzi, V.; Citoni, B.; Battistoni, A.; Ferrucci, A.; Volpe, M.
Abstract : Objective: Introduction. The prognostic significance of white-coat (WCHT) and masked hypertension (MHT) compared to normotension (NT) and sustained hypertension (SHT) is still debated. Aim. To evaluate prevalence and long-term clinical outcomes of NT, WHCT, MHT and SHT. Design and method: Methods. We analysed home, clinic and 24-hour ambulatory blood pressure (BP) levels from a large cohort of untreated adult outpatients who were consecutively evaluated at out Hypertension Unit between January 2007 and December 2015. The following definitions were applied: NT (clinic BP <140/90 mmHg; 24-hour BP <130/80 mmHg), WCHT (clinic BP > = 140/90 mmHg; 24-hour BP <130/80 mmHg), MHT (clinic BP <140/90 mmHg; 24-hour BP > = 130/80 mmHg), and SHT (clinic BP > = 140/90 mmHg; 24-hour BP > = 130/80 mmHg). Systematic research throughout the regional medical database was performed to estimate incidence of myocardial infarction, stroke and hospitalizations for HT and heart failure (HF). Results: Results. Among a total study sample of 2, 209 adult untreated individuals, 377 (17.1%) had NT, 351 (15.9%) WCHT, 149 (6.7%) MHT, and 1, 332 (60.3%) SHT. During an average follow-up of 120.173.9 months, WCHT was associated to reduced risk of developing stable HT [OR 95% CI: 0.593 (0.450–0.780); P < 0.001] and high risk of hospitalization for HT [OR 95% CI: 1.927 (1.233–3.013); P = 0.04] and HF [OR 95% CI: 3.449 (1.321–9.007); P = 0.011], whereas MHT was associated to an increased risk of myocardial infarction [OR 95% CI: 5.090 (2.228–11.625);P < 0.001], hospitalization for HT [OR 95% CI: 2.553 (1.446–4.508); P = 0.001] and HF [OR 95% CI: 4.214 (1.449–12.249); P = 0.008] compared to SHT. Conclusions: Conclusions. Our findings confirmed that, despite relatively low prevalence, both WCHT and MHT were associated to high of developing myocardial infarction and hospitalizations for HT and HF.